Le fratture articolari ed extra-articolari del ginocchio - Rocca, G.; Colasanto, G.; De Venuto, A.; De Sal, A. (Lo Scalpello - Journal, 2018)
ARTICULAR AND EXTRA-ARTICULAR KNEE FRACTURESJoint fractures of the knee include epiphyseal detachments of the distal femur and proximal tibia (types 3 and 4according to Salter-Harris). Extra-articular fractures include: avulsion of the tibial spines, detachment of the anteriortuberosity and patellar fractures. Fractures involving the distal femoral and proximal tibial epiphysis are relativelyinfrequent but may lead to long-term complications owing to the formation of post-traumatic bone bridges. Unlessthe fracture is composed, surgical treatment is always indicated. Avulsion fractures of the tibial spines occur as a resultof a chondro-epiphyseal detachment of the insertion of the cruciate ligaments (predominantly the anterior one). Theyare infrequent injuries (3 per 100,000 cases per year, 2% of all knee injuries). Accurate diagnosis and appropriatetreatment prevent unfortunate outcomes. Adolescent tibial tubercle fractures are uncommon, high-energy injuriessometimes combined with patellar tendon rupture; they represent a frequently missed diagnosis. Openreduction/internal fixation is generally required. Patellar fractures are caused by direct trauma (primary osseousfractures) or by an eccentric load during extension of the knee (sleeve and avulsion fractures). Most fractures requireopen reduction/internal fixation. The complication rate is low but late reconstruction of missed injuries may result inan extensor deficit.